2008
DOI: 10.1177/1352458508091368
|View full text |Cite
|
Sign up to set email alerts
|

Atorvastatin decreases high-sensitivity C-reactive protein in multiple sclerosis

Abstract: The anti-inflammatory potential of 3-hydroxy-3-methylglutaryl coenzyme A reductase inhibitors, as reflected by modulation of C-reactive protein (CRP), might be beneficial in the treatment of patients with multiple sclerosis (MS). We evaluated serum levels of high-sensitivity (hs)-CRP in relapsing-remitting MS patients receiving interferon-beta 1b and atorvastatin as add-on therapy. This study shows that interferon-beta treatment is associated with increased serum levels of hs-CRP in MS patients (P<0.01). In co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 14 publications
0
15
0
Order By: Relevance
“…Inflammation can be initiated by factors such as microbiological, immunological and toxic agents [17], and infectious agents have been reported to be associated with MS [18][19][20]. Furthermore, C-reactive protein has been used as an inflammatory marker in assessing inflammation in MS patients [21,22]. Therefore, the metabolic abnormalities reported here in membrane MUFAs from patients as measured against the CRP indicated a possible functional loss during inflammatory activation.…”
Section: Discussionmentioning
confidence: 89%
“…Inflammation can be initiated by factors such as microbiological, immunological and toxic agents [17], and infectious agents have been reported to be associated with MS [18][19][20]. Furthermore, C-reactive protein has been used as an inflammatory marker in assessing inflammation in MS patients [21,22]. Therefore, the metabolic abnormalities reported here in membrane MUFAs from patients as measured against the CRP indicated a possible functional loss during inflammatory activation.…”
Section: Discussionmentioning
confidence: 89%
“…In the case of statins as add-on to IFNb therapy, preliminary trials have indicated positive results regarding the latter two in that even high-dose statin supplementation has been well tolerated. Combinational therapy between these drugs would seem like an attractive option given the reliable safety profile of both drugs and that statins seem to decrease levels of circulating C-reactive protein in patients with MS [38]. C-reactive protein is involved in the IFNb-related side effect of post-injection flu-like symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…• Proportion of patients experiencing influenzalike symptoms (this specific outcome was chosen as statins seem to decrease levels of circulating C-reactive protein in patients with MS [38] and as C-reactive protein is involved in the IFNb-related side effect of post-injection flu-like symptoms).…”
Section: Outcomes Assessed In This Reviewmentioning
confidence: 99%
“…The end result is interruption of key signal transduction pathways vital for numerous functions of immune-competent cells. Other mechanisms were also reported such as decreasing migration of leukocytes across biological membranes [21] and diminishing C-reactive protein [22].…”
Section: Special Report Awad Sellner Hemmer and Stüvementioning
confidence: 98%